Mean stream coordinates structure of the Subantarctic Front: Temperature, salinity, and absolute velocity - Meinen, Christopher S.; Luther, Douglas S.; Watts, D. Randolph; Chave, Alan D.; Tracey, Karen L. (Journal of Geophysical Research: Oceans, 2003)
The mean synoptic structure of the northern, strongest branch of the Antarctic Circumpolar Current southwest of Tasmania, at the Subantarctic Front (SAF), is estimated by a stream coordinates analysis of data from overlapping arrays of Inverted Echo Sounders (IESs) and Horizontal Electric Field Recorders deployed during the 1995-1997 Sub-Antarctic Flux and Dynamics Experiment. The stream coordinates are derived from a daily objective mapping of the temperature field obtained from combining the IES travel time measurements with an empirical look-up table constructed from the extensive hydrography acquired during WOCE. Full-water-column stream-coordinates sections of temperature, Salinity, and absolute velocity are presented and compared with prior observations. The along-stream current has a single peak with surface velocities reaching about 50 cm s-1. The vertical structure of the along-stream velocity is roughly consistent with a combined external and first internal normal mode description that is adapted to the buoyancy frequency as it varies across the front, although there are some significant differences. The cross-stream structure of along-stream velocity is very nearly symmetric about the jet axis, but the lateral shear magnitude is slightly larger on the cold side of the SAF. Separating the baroclinic and barotropic currents reveals that the SAF currents are diffluent, primarily baroclinically, in the cross-stream direction. Baroclinic cross-stream diffluence of approximately 0.23 Sv per km (Sv = 106 m3 s-1), or about 16 Sv per degree of longitude at 51°S. The 2-year mean total SAF transport is 75 Sv (for a 220 km width); the barotropic contribution is small (8 Sv) but not negligible.